Efektivitas Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Berbantukan Media Teka-Teki Silang (TTS) pada Pembelajaran Sejarah Siswa Kelas XI di SMAS Sirajul Ibad Aceh Selatan - Suwirda, *Eva; Zulfan, Zulfan (Universitas Syiah Kuala, 2021)
This study discusses the application of the Teams Games Tournament (TGT) cooperative learning model with the aid of Crossword Puzzles (TTS) in the history learning of Class XI students at SMAS Sirajul Ibad Aceh Selatan to find out whether the application of the model is effective in increasing history learning activities. This study uses a qualitative approach with the type of research that is descriptive. The subjects in this study used a purposive sampling technique. In this study, the subjects were students of class XI SMAS Sirajul Ibad with a total of 20 students. The object in this research that will be examined is the effectiveness of the application of the Teams Games Tournament (TGT) cooperative learning model assisted by Crossword Puzzles (TTS) in learning history for Class XI students at SMAS Sirajul Ibad, South Aceh. Data collection techniques using observations and documentation. Based on the results of the study, the application of the Teams Games Tournament (TGT) cooperative learning model with the help of Crossword Puzzles (TTS) in class XI at SMAS Sirajul Ibad Aceh Selatan was carried out according to the lesson plan and was effective in increasing student learning activity. This is evidenced by the active participation of students during the learning process and achieving the predetermined indicators of learning activity while at the same time succeeding in achieving the learning objectives. Through observation during the learning process, student activity changes, students who were previously inactive become more active. Overall, the level of student activity in history learning got a score of 83% with a very good category.